2018
DOI: 10.1111/jipb.12657
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the regulation of C‐repeat binding factors in plant cold signaling

Abstract: Cold temperatures, a major abiotic stress, threaten the growth and development of plants, worldwide. To cope with this adverse environmental cue, plants from temperate climates have evolved an array of sophisticated mechanisms to acclimate to cold periods, increasing their ability to tolerate freezing stress. Over the last decade, significant progress has been made in determining the molecular mechanisms underpinning cold acclimation, including following the identification of several pivotal components, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
123
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 174 publications
(123 citation statements)
references
References 131 publications
(238 reference statements)
0
123
0
Order By: Relevance
“…Even in the ice1‐2 ice2‐1 double mutant, the cold‐induced expression of CBF and COR genes is only partially affected, which suggests that additional transcription factors are involved in the regulation of CBF genes (Liu et al 2018). Our ChIP‐seq data revealed ICE1 binding to the promoters of several other transcription factors critical for cold response including CAMTA2 and to the promoters of other important regulators of cold response including MPK3, MPK4 and HOS1 (Table S1).…”
Section: Accession Numbermentioning
confidence: 99%
“…Even in the ice1‐2 ice2‐1 double mutant, the cold‐induced expression of CBF and COR genes is only partially affected, which suggests that additional transcription factors are involved in the regulation of CBF genes (Liu et al 2018). Our ChIP‐seq data revealed ICE1 binding to the promoters of several other transcription factors critical for cold response including CAMTA2 and to the promoters of other important regulators of cold response including MPK3, MPK4 and HOS1 (Table S1).…”
Section: Accession Numbermentioning
confidence: 99%
“…Recent studies showed that ICE1 protein is phosphorylated by protein kinases, including OST1 (open stomata 1) and MPK3/6 in Arabidopsis, and OsMAPK3 in rice (Ding et al, 2015;Li et al, 2017a;Zhang et al, 2017;Zhao et al, 2017;Shi et al, 2018). More recently, OST1 was found to interact with and phosphorylate BTF3 proteins, b-subunits of a nascent polypeptide-associated complex (NAC), and enhances their interaction with CBF proteins, thereby stabilizing CBF proteins under cold stress Liu et al, 2018). Importantly, ICE1 is stabilized under cold stress after phosphorylation by cold-activated OST1, thereby promoting plant freezing tolerance (Ding et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, ICE1 is stabilized under cold stress after phosphorylation by cold-activated OST1, thereby promoting plant freezing tolerance (Ding et al, 2015). More recently, OST1 was found to interact with and phosphorylate BTF3 proteins, b-subunits of a nascent polypeptide-associated complex (NAC), and enhances their interaction with CBF proteins, thereby stabilizing CBF proteins under cold stress Liu et al, 2018). Nevertheless, the molecular mechanism underlying cold activation of OST1 remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…So far, the most in‐depth cold signal transduction pathway in plants is called CBF regulon, which is well reviewed in Shi et al (2015), Liu et al (2018b), Shi et al (2018) and Ding et al (2019). Expressions of the cold responsive genes COLD REGULATED ( CORs ) are regulated by DEHYDRATION‐RESPONSIVE ELEMENT BINDING FACTORS ( DREBs )/ CBFs (Gilmour et al 1998; Liu et al 1998).…”
Section: Chilling Signal Transduction In Ricementioning
confidence: 99%